Changes in surgical revascularization strategy after fractional flow reserve. Issue 3 (10th April 2021) - Fournier, Stephane; Toth, Gabor G; De Bruyne, Bernard; Kala, Petr; Ribichini, Flavio L; Casselman, Filip; Ramos, Ruben; Piroth, Zsolt; Piccoli, Anna; Penicka, Martin; Mates, Martin; Nemec, Petr; et al.
Abstract: Aims: In the randomized GRAFFITI trial, surgeons drew their strategy based on coronary angiography. When patients were randomized to fractional flow reserve (FFR)‐guidance, surgeons were informed of the FFR values and asked to redraw their strategy. The aim of this study was to investigate the changes induced by FFR knowledge. Methods and Results: The intended and performed strategy (before and after FFR) were compared. Among 172 patients, 84 with 300 lesions were randomized to the FFR‐guided group. The intended strategy was to bypass 236 stenoses:108 with a venous and 128 with an arterial graft. After disclosing FFR, a change in strategy occurred in 64 lesions (21.3%) of 48 (55%) patients. Among 64 lesions for which the intended strategy was medical therapy, 16 (25%) were bypassed after disclosing FFR. The number of procedures with >1 venous graft planned was significantly reduced from 37 to 27 patients ( p = .031). The proportion of on‐pump surgery was significantly reduced from 71 to 61 patients ( p = .006). The rates of clinical events at 1 year were similar between patients with or without at least one change in strategy. Discussion: FFR‐guided CABG is associated with a simplified surgical procedure in 55% of the patients, with similar clinical outcomes.